In vivo toxicity of chitosan-based nanoparticles: a systematic review - Shela Salsabila; Miski Aghnia Khairinisa; Nasrul Wathoni; Irna Sufiawati; Wan Ezumi Mohd Fuad; Nur Kusaira Khairul Ikram; Muchtaridi Muchtaridi (Artificial Cells, Nanomedicine, and Biotechnology)
Chitosan nanoparticles have been extensively utilised as polymeric drug carriers in nanoparticles formulations due to their potential to enhance drug delivery, efficacy, and safety. Numerous toxicity studies have been previously conducted to assess the safety profile of chitosan-based nanoparticles. These toxicity studies employed various methodologies, including test animals, interventions, and different routes of administration. This review aims to summarise research on the safety profile of chitosan-based nanoparticles in drug delivery, with a focus on general toxicity tests to determine LD50 and NOAEL values. It can serve as a repository and reference for chitosan-based nanoparticles, facilitating future research and further development of drugs delivery system using chitosan nanoparticles. Publications from 2014 to 2024 were obtained from PubMed, Scopus, Google Scholar, and ScienceDirect, in accordance with the inclusion and exclusion criteria.The ARRIVE 2.0 guidelines were employed to evaluate the quality and risk-of-bias in the in vivo toxicity studies. The results demonstrated favourable toxicity profiles, often exhibiting reduced toxicity compared to free drugs or substances. Acute toxicity studies consistently reported high LD50 values, frequently exceeding 5000 mg/kg body weight, while subacute studies typically revealed no significant adverse effects. Various routes of administration varied, including oral, intravenous, intraperitoneal, inhalation, and topical, each demonstrating promising safety profiles.